2017
DOI: 10.1177/1368430216683531
|View full text |Cite
|
Sign up to set email alerts
|

How do social beliefs affect political action motivation? The cases of Russia and Ukraine

Abstract: Political action is one of the main methods of social change. Previous research has shown that readiness to participate in such actions is determined by an evaluation of the current situation. The question arises as to how stable beliefs influence such evaluations. In this study we have analyzed the link between such beliefs and readiness to participate in political actions. We assumed that just and dangerous world beliefs are factors that influence readiness to participate in political actions. However, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…To our knowledge, the current research is one of the few comprehensive empirical investigations of the predictors of collective action tendencies in contexts where protesters face substantial risks due to state repression. Unlike past research, which was predominantly conducted in WEIRD (western, educated, industrialized, rich, and democratic;Henrich, Heine, & Norenzayan, 2010;Rad, Martingano, & Ginges, 2018) contexts, this paper presents some of only a handful of studies on the social-psychological predictors of collective action in high-risk contexts (for exceptions see Ayanian & Tausch, 2016;Baysu & Phalet, 2017;Gulevich, Sarieva, Nevruev, & Yagiyayev, 2017;Chayinska, Minescu, & McGarty, 2017). These data are unique given the practical difficulty of gathering data from activists in such contexts.…”
Section: Contributions and Directions For Future Researchmentioning
confidence: 99%
“…To our knowledge, the current research is one of the few comprehensive empirical investigations of the predictors of collective action tendencies in contexts where protesters face substantial risks due to state repression. Unlike past research, which was predominantly conducted in WEIRD (western, educated, industrialized, rich, and democratic;Henrich, Heine, & Norenzayan, 2010;Rad, Martingano, & Ginges, 2018) contexts, this paper presents some of only a handful of studies on the social-psychological predictors of collective action in high-risk contexts (for exceptions see Ayanian & Tausch, 2016;Baysu & Phalet, 2017;Gulevich, Sarieva, Nevruev, & Yagiyayev, 2017;Chayinska, Minescu, & McGarty, 2017). These data are unique given the practical difficulty of gathering data from activists in such contexts.…”
Section: Contributions and Directions For Future Researchmentioning
confidence: 99%
“…It worth noting that in parallel to ESIM, a large amount of social-psychological research mainly draws upon the social identity model of collective action (SIMCA; van Zomeren, Postmes, & Spears, 2008) and has explored diverse antecedents that may predict people's participation in different forms of collective action including protest violence. In particular, some of those studies have suggested that social beliefs about how fair or dangerous the world is (Gulevich, Sarieva, Nevruev, & Yagiyayev, 2017), and certain implicit theories about social change (Shuman, Cohen-Chen, Hirsch-Hoefler, & Halperin, 2016) may increase people's readiness and willingness to carry out violent actions during protests (e.g., throw stones or bottles, clashing with the police). In addition, researchers have also suggested that certain emotions (i.e., anger and contempt) are critical to predict people's intentions to carry out non-violent or violent actions respectively (see Becker, Tausch, & Wagner, 2011;Tausch et al, 2011).…”
Section: Violence During Social Mobilisation Processesmentioning
confidence: 99%
“…The next triad of papers analyse and study collective action within (typically national) cultural contexts , ranging from Southern Italy ( Travaglino, Abrams, & Russo, 2017 ) to New Zealand ( Osborne, Yogeeswaran, & Sibley, 2017 ) and Turkey ( Baysu & Phalet, 2017 ). The final four papers ( Chayinska, Minescu, & McGarty, 2017 ; Fischer, Becker, Kito, & Nayir, 2017 ; Górska, Bilewicz, & Winiewski, 2017 ; Gulevich, Sarieva, Nevruev, & Yagiyayev, 2017 ) analyse multiple samples across (again typically national) cultural contexts (i.e., Germany, Croatia, Hungary, Japan, Latvia, Lithuania, Poland, Russia, Turkey, and Ukrain) and also deal with issues such as comparability of samples and measurement equivalence.…”
Section: A Preview Of the Contributions To The Special Issuementioning
confidence: 99%